Perbedaan Siriraj Stroke Score (3S) & Dave and Djoenadi Stroke Score System (3S2D) Terhadap Durasi Penentuan Diagnosa Keperawatan Pasien Stroke di IGD - Jamilah, Siti; Mohtar, M. Sobirin; Tjomiadi, Cynthia Eka Fayuning; Santoso, Bagus Rahmat (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Stroke patient service in the emergency room provided by nurses and must do it quickly, effectively, and efficiently, this can be achieved with the right assessment instrument. Knowing the difference in the assessment of Siriraj Stroke Score (3S) and Dave and Djoenaidi Stroke Score System (3S2D) on the duration of determining the nursing diagnosis of stroke patients in the emergency room. Quantitative research with one group post test only design, and sampling using purposive sampling of 30 respondents. The statistical test uses the Paired Sample T-test test. The results of the Paired Sample T-test test showed that the average difference in the duration of determining nursing diagnoses in 3S and 3S2D assessment was 7.6 minutes. The lowest difference is 7.1 minutes, and the highest difference is 8.1 minutes. It is known that the t value is 29.135> t table 2.045 and Sig. value of 0.000 <0.05. The use of the 3S assessment method is more compatible to be used during emergencies because the assessment method is simple and fast, while the 3S2D assessment is quite time consuming so that this assessment will be easier if it is carried out by 2 nurses